Polydatin-Mediated Inhibition of HSP90α Disrupts NLRP3 Complexes and Alleviates Acute Pancreatitis - Jiashu Yang; Chenyang Jiao; Nannan Liu; Wen Liu; Yueyao Wang; Ying Pan; Lingdong Kong; Wenjie Guo; Qiang Xu (Research)
The NLRP3 inflammasome plays a critical role in various inflammatory conditions. However, despite extensive research in targeted drug development for NLRP3, including MCC950, clinical success remains elusive. Here, we discovered that the activated NLRP3 inflammasome complex (disc-NLRP3) and the activating mutation L351P exhibited resistance to MCC950. Through investigations using the small-molecule compound polydatin, HSP90α was found to stabilize both the resting (cage-NLRP3) and activated state (disc-NLRP3) of NLRP3 complexes, sustaining its activation. Our mechanistic studies revealed that polydatin specifically targets HSP90α, binding to it directly and subsequently interfering with the HSP90α-NLRP3 interaction. This disruption leads to the dissipation of cage-NLRP3, disc-NLRP3 complexes and NLRP3 L351P. Importantly, genetic and pharmacological inactivation of HSP90α effectively reduced NLRP3 inflammasome activation and alleviated cerulein-induced acute pancreatitis. These therapeutic effects highlight the clinical potential of HSP90α inhibition. Our findings demonstrate that HSP90α is crucial for the stability of both the resting and activated states of the NLRP3 inflammasome during its sustained activation, and targeting HSP90α represents a promising therapeutic strategy for diseases driven by the NLRP3 inflammasome.